The Persian–Portuguese encounter in Hormuz: orientalism reconsidered - Tazmini, G. (Iranian Studies, 2017)
In 2015, the quincentennial commemoration of the Portuguese arrival on the island of Hormuz in the Persian Gulf (1515–1622) revealed the underlying presupposition among Iranians that the Portuguese presence on the island was the harbinger of a long-term pattern of western imperialism. This analysis questions the accuracy of this narrative by advancing a new interpretative framework that does not reduce the holding of Hormuz to simply another dark episode of European colonial history. Circumscribed and limited in aim and reach, Lusitanian activities on Hormuz cannot be brought under the generic rubric of “orientalism,” which is embedded in European colonial tradition, and which, by extension, buttresses Iranian nationalist sentiment about the Persian–Portuguese entanglement. This research demonstrates that Portuguese objectives diverged from the eighteenth and nineteenth century rationalist scientific traditions of the British, French and Germans professing a civilizing mission as a rationale for colonial policies. Whereas the Portuguese operated from a worldview that combined profit, dynastic pride and religious rhetoric, the Portuguese mission to Hormuz was not guided by a grand discourse of civilizing the “other.” While there was a complex interplay of commercial interests and brutal methods on this strategic entrepôt, Portuguese ambitions in Hormuz were confined and elusive, and at best a matter of tribute-taking. The present paper charters some of these complex interactions.